Physical Fitness Of Extracurricular Students Pencak Silat Tanding Category Reviewed From Endurance And Body Mass Index - Fika Umi Latifah; Gatot Jariono (Universitas Bengkulu, 2021)
The sample in this study was extracurricular students coaching the achievement of Pencak silat match category in Gemolong District Elementary School Sragen Regency of Central Java Province who participated in training 1 year or more aged 10-12 years as many as 30 students with the provisions of 15 male and 15 female. Quantitative descriptive methods are used in this study while a data analysis technique uses percentage descriptive analysis. The results of this study can be concluded that the physical fitness of extracurricular students Pencak silat match category is reviewed from moderate category endurance for male and less category for female while body mass index characteristics in the category of normal weight. This study only describes physical fitness in terms of endurance and body mass index of elementary school students. For further research will be conducted experimental research with physical fitness training methods by the characteristics of elementary school students who follow extracurricular pencak silat in the counter category as qualified performance support